INDICATION OF CARIES FREE PREVALENCE AMONG 12 YEARS OLD STUDENTS IN IZEH CITY - M MOUSAVINASAB; F SHEYKHI (Journal of Research in Medical Sciences, 2003)
Introduction: Caries is a factor of teeth missing and its prevalence and also its expenditure are very light in Iran. Treatment ways need a lot of time, but they have little success, so it is important to prevent caries. Now if we want to have a successful model, having person's statistics is important and useful for our Research purposes. This research was done to detect caries free prevalence in students twelve year of age in Izeh city and it contained 2groups of girls and boys. It was done to indicate the connection between caries free prevalence and individual oral hygiene with brushing times, numbers during 24 hours.
Methods: This research is a kind of epidemiological and descriptive study. It was done in Izeh city in 78-79 educational years. Its only document, was selection the 12 years old students.
Informations collected by clinical inspections and interrogatory J method
Sample volume was 400 students according to this formula N=Z2(1-p)/ d2. We use Chi-square statistics test and also its soft disk (SPSS) or statitistics program was about social science.
Conclusion: Caries free prevalence within the whole sample was 16.5%and it was 17.5% within the girls and 15-5% within boys.
According to brushing times numbers, 25% brushed once a day, 47% brushed twice and 5.5% brushed three time a day and 22.5% never brushed their teeth.
Discussin and conclusion: According to the obtained dates, caries prevalence related to sex difference was meaningless and they had no connection with each other there was a meaningful connection between brushing times, numbers and oral hygiene situation which caries free developed by increasing anyone of them.